Physical activity coaching for adults with mobility limitations: protocol for the ComeBACK pragmatic hybrid effectiveness-implementation type 1 randomised controlled trial. Issue 11 (3rd November 2020) - Hassett, Leanne; Tiedemann, Anne; Hinman, Rana S; Crotty, Maria; Hoffmann, Tammy; Harvey, Lisa; Taylor, Nicholas F; Greaves, Colin; Treacy, Daniel; Jennings, Matthew; Milat, Andrew; Bennell, Kim L; et al.
Abstract : Introduction: Mobility limitation is common and often results from neurological and musculoskeletal health conditions, ageing and/or physical inactivity. In consultation with consumers, clinicians and policymakers, we have developed two affordable and scalable intervention packages designed to enhance physical activity for adults with self-reported mobility limitations. Both are based on behaviour change theories and involve tailored advice from physiotherapists. Methods and analysis: This pragmatic hybrid effectiveness-implementation type 1 randomised control trial (n=600) will be undertaken among adults with self-reported mobility limitations. It aims to estimate the effects on physical activity of: (1) an enhanced 6-month intervention package (one face-to-face physiotherapy assessment, tailored physical activity plan, physical activity phone coaching from a physiotherapist, informational/motivational resources and activity monitors) compared with a less intensive 6-month intervention package (single session of tailored phone advice from a physiotherapist, tailored physical activity plan, unidirectional text messages, informational/motivational resources); (2) the enhanced intervention package compared with no intervention (6-month waiting list control group); and (3) the less intensive intervention package compared with no intervention (waiting list control group). The primary outcome will be average steps per day, measured with the StepWatch Activity Monitor over a 1-week period, 6 months after randomisation. Secondary outcomes include other physical activity measures, measures of health and functioning, individualised mobility goal attainment, mental well-being, quality of life, rate of falls, health utilisation and intervention evaluation. The hybrid effectiveness-implementation design (type 1) will be used to enable the collection of secondary implementation outcomes at the same time as the primary effectiveness outcome. An economic analysis will estimate the cost-effectiveness and cost-utility of the interventions compared with no intervention and to each other. Ethics and dissemination: Ethical approval has been obtained by Sydney Local Health District, Royal Prince Alfred Zone. Dissemination will be via publications, conferences, newsletters, talks and meetings with health managers. Trial registration number: ACTRN12618001983291.